The Development of Android-Based Mobile Learning on Materials for Preparation and Proclamation of Indonesian Independence for Class VIII Blind Students at MTs Yaketunis Yogyakarta - Hakim, Yusuf; Sujarwo (JTP - Jurnal Teknologi Pendidikan, 2022)
This research aims to find out the feasibility of mobile learning product. This research refers to the development model by Alessi & Trollip. The procedure of mobile learning development consists of (1) planning, (2) designing, and (3) developing that was equipped with component attributes including standards, ongoing evaluation, and project management. The product testing consists of alpha test assessed by media experts, material experts, and instructional experts, while, the beta test involvs impairment students. The data collection techniques used questionnaire. The instrument of data collections used questionnaire. The data analysis techniques used descriptive analysis techniques. The research results showed the feasibility of the product was considered as highly-feasible based on the assessment of media experts, material experts, instructional experts, and the first students’ responses.